Conopeptides [V11L;V16D]ArIB and RgIA4: Powerful Tools for the Identification of Novel Nicotinic Acetylcholine Receptors in Monocytes - Grau, Veronika; Richter, Katrin; Hone, Arik J.; McIntosh, J. Michael (Frontiers in Pharmacology, 2019)
Abstract Venomous marine snails of the genus Conus employ small peptides to capture prey, mainly osteichthyes, mollusks, and worms. A subset of these peptides known as α-conotoxins, are antagonists of nicotinic acetylcholine receptors (nAChRs). These disulfide-rich peptides provide a large number of evolutionarily refined templates that can be used to develop conopeptides that are highly selective for the various nAChR subtypes. Two such conopeptides, namely [V11L;V16D]ArIB and RgIA4, have been engineered to selectively target mammalian α7* and α9* nAChRs, respectively, and have been used to study the functional roles of these subtypes in immune cells. Unlike in neurons and cochlear hair cells, where α7* and α9* nAChRs, respectively, function as ligand-gated ion channels, in immune cells ligand-evoked ion currents have not been demonstrated. Instead, different metabotropic functions of α7* and α9* nAChRs have been described in monocytic cells including the inhibition of ATP-induced ion currents, inflammasome activation, and interleukin-1β (IL-1β) release. In addition to conventional nAChR agonists, diverse compounds containing a phosphocholine group inhibit monocytic IL-1β release and include dipalmitoyl phosphatidylcholine, palmitoyl lysophosphatidylcholine, glycerophosphocholine, phosphocholine, phosphocholine-decorated lipooligosaccharides from Haemophilus influenzae, synthetic phosphocholine-modified bovine serum albumin, and the phosphocholine-binding C-reactive protein. In monocytic cells, the effects of [V11L;V16D]ArIB and RgIA4 suggested that activation of monocytic nAChRs containing α9, α7 and/or α10 subunits inhibits ATP-induced IL-1β release. These results have been corroborated utilizing gene-deficient mice and small interfering RNA. Targeted re-engineering of native α-conotoxins has resulted in excellent tools for nAChR research as well as potential therapeutics. *indicates possible presence of additional subunits.